Strategi Komunikasi Perempuan Dalam Menghindari Cyber Crime Pada Aplikasi Dating Online Tinder - Yulistiawan, Tasyadilla Nur Azmi; Juwita, Rina (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
Along with the rapid advancement of information and communication technology, the use of online dating applications is now widely used by various groups. The use of this application is considered to help individuals find friends and even partners. One of the online dating applications that is trending among them is Tinder. With the "swipe right" and "swipe left" features as well as the distance and age filters presented, Tinder has successfully become an online dating application that has successfully attracted many users around the world, one of which is Indonesia. However, behind the success of this application as a bridge for introduction between individuals, various problems have emerged such as cybercrime. The victims of cybercrime that occur on this online dating application are mostly women. This study aims to analyze women's communication strategies in avoiding cybercrime on the Tinder online dating application. The method used in this study is a descriptive qualitative approach with in-depth interviews and participatory observation with five Tinder user informants in Samarinda. This study uses the theory of communication privacy management, uncertainty reduction theory, and symbolic interaction theory to analyze the strategies used by women in avoiding cybercrime in using the Tinder application. The results found in this study indicate that female users of the online dating application Tinder have a high awareness of the risks of cybercrime and use effective communication strategies to protect themselves, including limiting personal information, verifying the identity of potential partners, utilizing the application's security features, and sharing information with other users.